A NATURALISTIC STUDY ON COMMUNICATION STRATEGY USED BY THE SECOND SEMESTER STUDENTS IN SPEAKING CLASS OF ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH SURAKARTA - Anggraini, Dini Inge (JoLLIET, 2016)
This research aims to describe the communication strategies used by secondsemester students in Speaking class of Universitas Muhammadiyah Surakarta.The study is also as a reference for the better problem-management in teachinglearningprocess. The data of research contain communication strategies usedbythe second semester students in Speaking class of English EducationDepartment of Universitas Muhammadiyah Surakarta in 2015/2016 academicyear. The sources of data are derived from event, informant, and document. Thewriter investigates classes of Speaking, with 8 students as the subjects of theresearch. The writer uses descriptive qualitative method in analyzing the data.The data are based on Celce-Murcia taxonomy of communication strategies.The result of this study shows that there are five types with fourteen subtypes ofcommunication strategies, the most dominant types of communication strategiesused by second semester students in Speaking class is fillers with 31,05%, andthe rarely type of communication strategies used by students are topicavoidance, word coinage, literal translation, self-initiated repair with 0,53%.The result above implies that teaching communication strategies is needed forstudents who still have limited knowledge in the target language. To maintainstudentsâ communication, communication strategies as a subject in Speakingclass will make the students aware when they communicate with the others.Key words: communication strategies, speaking